Integrating spirituality and psychotherapy : experiences of a sample of terminally ill patients - Chemane, Bonginkosi Reginald (Rhodes University, Faculty of Humanities, Department of Psychology)
The general aim of this study was to determine the experiences of a sample of terminally ill patients in using spiritually focused psychotherapy. This was a qualitative study conducted to a sample of 2 terminally ill patients from hospice in Grahamstown, South Africa. The research was conducted in 3 phases: an initial in-depth interview conducted to determine the participants' level of spirituality as well as the extent to which their terminal illnesses had affected their functioning. This was followed by a minimum of 6 spiritually focused therapy (SFT) sessions as a second phase of the research. To determine the participants' experiences of SFT, 2-3 in-depth interviews were conducted during the 3m phase of the research study. The research revealed that a belief in a higher power helps terminally ill patients cope better with their illness and that social disconnectedness is related to HIV / AIDS stigma. It also revealed that terminal illness is co-morbid with other psychiatric symptoms such as depression, evokes existential concerns, results in a change in the level of spirituality and affects the whole family. Participants blamed themselves for their illness, but found that engaging in the process of forgiveness of self and others brought about psychological healing for them. They experienced SFT as a coping resource that assisted them to deal with the fear of death as well as increased insight into the development of psychopathology and spiritual blockages. It is recommended that a comprehensive and holistic assessment during intake be undertaken so that where spiritual needs are available, therapy can be spiritually augmented to ensure that such needs/ struggles are addressed.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Psychotherapy; Terminal care -- South Africa -- Grahamstown; Hospices (Terminal care); Terminally ill -- Psychology; Spiritual care (Medical care)